Intrinsic magnetic topological insulator phases in the Sb doped MnBi2Te4 bulks and thin flakes - Bo Chen (Nature Portfolio, 2019)
Available intrinsic magnetic topological insulators are rare. Here, the authors study the electronic and magnetic properties of Mn(Sb x Bi(1-x))2Te4 bulks and thin flakes, revealing intrinsic magnetic topological insulator phase in the phase diagram.